A molecular phylogeny of the genus Laubuka (Teleostei: Cyprinidae) in Sri Lanka reveals multiple origins and a cryptic species. Issue 6 (17th August 2020) - Sudasinghe, Hiranya; Pethiyagoda, Rohan; Meegaskumbura, Madhava
Abstract : The freshwater-fish genus Laubuka contains ∼13 species distributed through the lowlands of tropical South and South-east Asia. Four of these species ( Laubuka lankensis, L. varuna, L. ruhuna, and L. insularis ) are reported as endemic to Sri Lanka, a remarkable datum given the island's small size. We sampled populations of Laubuka at 56 locations in 14 of the island's principal river basins and analysed their morphological, meristic, phylogenetic, and phylogeographic relationships using the mitochondrial genes cytochrome b and cytochrome c oxidase subunit 1 and the nuclear recombination activating protein 1 . We investigated the geographic structure, and delineated species using molecular species delimitation methods and morphological analysis within the general lineage concept of species. Molecular and morphological analyses failed to identify L. ruhuna and L. insularis as distinct species; we show them to be synonyms of L. varuna and L. lankensis, respectively. Taxonomic inflation in previous literature is attributed as a result of limited sampling and negligence of size allometry. Additionally, a third, cryptic species discovered in this study is described as L. hema sp. nov. which is evidently confined to the headwaters of the Gal basin in eastern Sri Lanka. Phylogenetic and haplotype network analyses suggest phylogeographic structure within both the southwest-endemic L. varuna and the dry-zone endemic L. lankensis, but the former shows strong phylogeographic structure between adjacent basins. The Sri Lankan species of Laubuka do not form a monophyletic group: they stem from two dispersal or vicariance events, one involving the lineage that led to L. varuna in south-western Sri Lanka, and the other, of [ L. lankensis + L. hema ] in the dry zone. http://zoobank.org/urn:lsid:zoobank.org:pub:D2A29329-E0E7-447E-B316-81049212CCCB http://zoobank.org/urn:lsid:zoobank.org:act:920E5DC0-CEDC-4243-98C7-12CCF829CBCD